2019
DOI: 10.1002/cpe.5402
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning algorithms to detect DDoS attacks in SDN

Abstract: SummarySummary Software‐Defined Networking (SDN) is an emerging network paradigm that has gained significant traction from many researchers to address the requirement of current data centers. Although central control is the major advantage of SDN, it is also a single point of failure if it is made unreachable by a Distributed Denial of Service (DDoS) attack. Despite the large number of traditional detection solutions that exist currently, DDoS attacks continue to grow in frequency, volume, and severity. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(70 citation statements)
references
References 28 publications
0
70
0
Order By: Relevance
“…The DT and SVM algorithms have been selected because they have shown high performance in previous research in different applications of SDN [31]- [34]. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…The DT and SVM algorithms have been selected because they have shown high performance in previous research in different applications of SDN [31]- [34]. Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, selecting the improper features can lead to a significant drawback on the performance attainable by most wellknown classifiers. For better illustration, Santos et al [30] demonstrated that the SDN controller attacks have the worst classifications results achieved by different machine learning algorithms. This return to the fact that some of the important features used to detect the new SDN attack types are similar to normal traffic patterns due to the unique SDN architecture.…”
Section: Background a Literature Reviewmentioning
confidence: 99%
“…In 2019, Santos et al created an SDN testbed to generate the attack traffic dataset for analyzing the performance of some ML techniques [30]. The SDN network was simulated using the POX controller and Mininet tool.…”
Section: B Reviewer-2: Comparison Of Existing Testbeds With Proposedmentioning
confidence: 99%
“…Four machine learning algorithms, namely, the multilayer perceptron, SVM, decision tree (DT), and RF, are analyzed and compared in [23] to detect DDoS attacks in SDN. These algorithms are proposed to detect three types of DDoS attacks: flow table, bandwidth, and controller attacks.…”
Section: B Machine Learning Approachmentioning
confidence: 99%